Vikings. Season 4, Volume 2 [videorecording (DVD)] - Standen, Clive; Winnick, Katheryn; Fimmel, Travis, 1979- (Twentieth Century Fox Home Entertainment, 2017)
Follows Viking Ragnar Lothbrok and his family as Ragnar rises to become king of the Viking tribes.